2020
DOI: 10.5339/jemtac.2020.6
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Trauma Services in Saudi Arabia

Abstract: Trauma is a major public health problem in Saudi Arabia and a leading cause of mortality and morbidity in young age groups. In 2018, traumatic injuries caused by road traffic accidents were the leading cause of death after ischemic heart diseases. Therefore, a new road safety system is important to reduce the incidence of road accident trauma. First aid care by bystanders to road accidents must be improved to become an effective part of pre-hospital care and avoid aggravation. Moreover, trauma centers need fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…This surge in calls likely relates to the following: (i) An increase in suspected COVID-19 cases due to new guidelines for classifying any patient with cough or fever as infectious, and (ii) fear of transporting patients with fever, cough, or other symptoms of COVID-19 in personal vehicles leading to an increase in calls to EMS for an ambulance [ 16 ]. Saudi Arabia has a high proportion of EMS calls for trauma due to motor vehicle collisions [ 17 ]. Our data showed that the proportion of emergency cases related to trauma markedly decreased during the COVID-19 pandemic, which may be related to the establishment of different levels of curfew and mobility restriction and the occurrence of Ramadan during the period evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…This surge in calls likely relates to the following: (i) An increase in suspected COVID-19 cases due to new guidelines for classifying any patient with cough or fever as infectious, and (ii) fear of transporting patients with fever, cough, or other symptoms of COVID-19 in personal vehicles leading to an increase in calls to EMS for an ambulance [ 16 ]. Saudi Arabia has a high proportion of EMS calls for trauma due to motor vehicle collisions [ 17 ]. Our data showed that the proportion of emergency cases related to trauma markedly decreased during the COVID-19 pandemic, which may be related to the establishment of different levels of curfew and mobility restriction and the occurrence of Ramadan during the period evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The data indicated that medical and trauma callouts in particular had very high rates of nontransportation in both rural and urban areas. The reasons for this are not possible to determine in a cross-sectional analysis, but studies in Saudi Arabia report a lack of general awareness among the public regarding the role of EMS,[ 2 3 ] and specifically in relation to dealing with routine versus emergency health situations. This confusion may underpin the large numbers of callouts for potentially a relatively minor health concern.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that some of the issues again stem from the lack of understanding among the general public regarding the role of EMS in Saudi Arabia. [ 2 3 ] Education programs regarding the type of emergencies to call an EMS may assist in reducing the number of callouts that result in nontransportation. This is particularly relevant for the high rates of nontransportation for medical and trauma callouts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations